2008
DOI: 10.1002/pd.2109
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in chorionic villous samples at 11 weeks' gestation from women destined to develop preeclampsia

Abstract: It is assumed that the pathogenesis of PE is associated with pathophysiological alterations to trophoblasts in early gestation. Our study has directly proved that gene expressions relating to angiogenesis or oxidative stress are altered in the first trimester trophoblasts that go on to develop PE later. These results would put the basis for a possible screening method for PE by using residual CVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 32 publications
2
72
0
1
Order By: Relevance
“…The expression levels of Flt-1, ENG and VEGF in CVS tissue obtained from pregnant women who later developed PE were higher, and those of PlGF and HO-1 were lower, than those of normal pregnancies. 16 These findings indicate that the up-regulation of anti-angiogenic factors and the down-regulation of anti-oxidant factors have already occurred in first-trimester trophoblasts, 16 and that the alterations could be evaluated by the analysis of cellular RNA. All of these findings support the hypothesis that some mRNA expression of Flt-1, ENG, PlGF, VEGF and HO-1 is derived from circulating trophoblasts, and that the alteration of these mRNA levels may reflect mRNA alterations associated with the pathogenesis of PE in the placenta.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The expression levels of Flt-1, ENG and VEGF in CVS tissue obtained from pregnant women who later developed PE were higher, and those of PlGF and HO-1 were lower, than those of normal pregnancies. 16 These findings indicate that the up-regulation of anti-angiogenic factors and the down-regulation of anti-oxidant factors have already occurred in first-trimester trophoblasts, 16 and that the alterations could be evaluated by the analysis of cellular RNA. All of these findings support the hypothesis that some mRNA expression of Flt-1, ENG, PlGF, VEGF and HO-1 is derived from circulating trophoblasts, and that the alteration of these mRNA levels may reflect mRNA alterations associated with the pathogenesis of PE in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the expression levels of Flt-1, ENG, VEGF and transforming growth factor-b1 (TGFb1) were significantly higher in the CVS tissues from pregnant women who later developed PE, whereas the levels of PlGF, HO-1 and superoxide dismutase (SOD) were lower. 16 These findings suggest that the genes associated with angiogenesis and reduced anti-oxidant stress play crucial roles in the pathogenesis of PE, and that the measurement of the expression of these factors in maternal blood may enable the prediction of the onset of PE.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HO is expressed by trophoblasts, and its inhibition has been shown to result in defective trophoblast invasion in vitro (20). Human studies have also shown that levels of Hmox are decreased in patients with preeclampsia (21)(22)(23)(24)(25)(26)(27). Furthermore, the addition of sera from patients with preeclampsia led to decreased levels of Hmox in vitro (28).…”
Section: Heme Oxygenase Pathwaymentioning
confidence: 99%